Photo-oxidation studies of 4-(chloromethyl)phenyltrichlorosilane on silicon and titanium oxide - Ali Sabri, Nadirah; Alang Ahmad, Shahrul Ainliah (Asian Publication Corporation, 2016)
The rates of photo-oxidation of 4-(chloromethyl)phenyltrichlorosilane (CMPS) formed on titanium oxide (TiO2) and silicon oxide (SiO2) substrates were studied. The optimized self-assembly of CMPS films on SiO2 and TiO2 were investigated which subsequently used for comparing photochemical reactions by exposing samples under deep UV of 254 nm. Upon the UV irradiation, the tail group of CMPS monolayers; chloro benzyl group is converted to aldehyde group and further exposure leads to the formation of polar group (carboxylic acid) which generates surfaces with a high surface free energy and a hydrophilic character. Analyses of contact angle, Fourier transform infrared and X-ray photoelectron spectroscopy (XPS) were performed to monitor the products generated upon UV irradiation. It was found that highly efficient and rapid photo-oxidation was observed for CMPS on TiO2, a complete conversion within minutes compared to CMPS on SiO2. The use of TiO2 has shown that the rate is thrice faster than SiO2 which is efficient as a photocatalytic oxidation. The resulting carboxylic group terminated surface was subsequently derivatized using 2-amino-1,1,1-trifluoroethane (TFEA). Contact angle and XPS measurements of post-derivatization indicated that the surface functionalization was extensive.